Modeling developmental changes in print tuning in a transparent alphabetic orthography - Verhoeven, Ludo; Voeten, Marinus; Keuning, Jos (Frontiers in Neuroscience, 2022)
The development of print tuning involves the increased specificity and redundancy for orthographic representations. However, it is by no means clear how decoding accuracy and efficiency are related over the years and how it affects reading disability. In the present study, we monitored the development of accuracy and efficiency of decoding in Dutch as a relatively transparent orthography as a function of orthographic complexity and lexical status throughout the primary grades. There was clear evidence that development of decoding accuracy preceded development of decoding efficiency and that a certain threshold of accuracy is needed for decoding efficiency to evolve. Furthermore, it was shown that pseudoword decoding efficiency predicted growth in word decoding efficiency, especially for the higher levels of orthographic complexity. There was also evidence that accuracy precedes efficiency across different profiles of readers and that decoding strength can be defined as a function of orthographic complexity and lexicality.